2004
DOI: 10.1176/appi.ajp.161.5.896
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Thalamic Volume and Shape in Schizophrenia

Abstract: Thalamic volume was smaller than normal in schizophrenia patients, but only proportionate to reductions in reduced total cerebral volume. The presence of changes in thalamic shape and asymmetry suggest greater pathologic involvement of individual nuclei at its anterior and posterior extremes of the thalamic complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
136
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(155 citation statements)
references
References 52 publications
17
136
1
Order By: Relevance
“…These datasets were used because they represented a variety of MR scanning parameters, subcortical structures and diseases. In addition, the datasets have also been used in previously published work validating landmarkinitialized diffeomorphic image matching (Haller et al, 1997;Csernansky et al, 2000Csernansky et al, , 2004aWang et al, 2007b). The Huntington's Disease (HD) dataset consisted of 16 subjects (7 male, 9 female), mean age 37 (SD=11) years, possessing the HD gene but not yet diagnosed with the disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These datasets were used because they represented a variety of MR scanning parameters, subcortical structures and diseases. In addition, the datasets have also been used in previously published work validating landmarkinitialized diffeomorphic image matching (Haller et al, 1997;Csernansky et al, 2000Csernansky et al, , 2004aWang et al, 2007b). The Huntington's Disease (HD) dataset consisted of 16 subjects (7 male, 9 female), mean age 37 (SD=11) years, possessing the HD gene but not yet diagnosed with the disease.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, to test thalamus segmentation, we used a dataset consisting of four healthy controls, chosen randomly from the comparison set used by Csernansky et al (2004a). These images were acquired using a turbo-fast, low-angle shots sequence (TR=20ms, TE=5.4ms, N=1, flip angle=30°, t=13.5min) with image dimensions 256 × 256 × 256 and voxel dimensions 1 × 1 × 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Several in vivo imaging and postmortem studies have failed to find abnormalities in thalamic volume or neuronal number in schizophrenic subjects (Portas et al, 1998;Arciniegas et al, 1999;Deicken et al, 2002;Cullen et al, 2003;Dorph-Petersen et al, 2004;Preuss et al, 2005). Moreover, recent neuroimaging analyses of the hippocampus (Csernansky et al, 2002) and thalamus (Csernansky et al, 2004) in the same cohort of schizophrenic subjects has indicated that pathology of one or the other structure may be more pronounced in different individuals (Csernansky, personal communication).…”
Section: Comparable Cell Number In Schizophrenic and Control Subjectsmentioning
confidence: 99%
“…In vivo neuroimaging studies of schizophrenic subjects have found smaller whole thalamic volume and altered thalamic shape (Ettinger et al, 2001;Gilbert et al, 2001;Csernansky et al, 2004), altered metabolic activity (Buchsbaum et al, 1996Hazlett et al, 1999 and reduction of volume in subregions or specific nuclei of the thalamus (Andreasen et al, 1994;Byne et al, 2001;Kemether et al, 2003). In addition, postmortem studies of brains from schizophrenic subjects have reported a reduction in total neuronal number and volume of individual thalamic nuclei, e.g., the mediodorsal, anterior, pulvinar and ventral lateral posterior nuclei (Pakkenberg, 1990;Popken et al, 2000;Young et al, 2000;Byne et al, 2002;Danos et al, 2002;.…”
Section: Introductionmentioning
confidence: 99%
“…Following the pioneering work by Bookstein, Grenander and Bajscy [4], [8], [22], the past several years have seen an explosion in the use of template matching methods in computer vision and medical imaging [3], [14], [24], [25], [30], [33], [36]- [40], [51], [53]- [56]. These methods have enabled the systematic measurement and comparison of anatomical shapes and structures in biomedical imagery leading to better understanding of neurodevelopmental, neuropsychiatric and neurological disorders in recent years [5], [6], [11], [13], [17], [20], [42]- [48], [50], [52], [59]. The mathematical theory of Grenander's deformable template models, when applied to these problems, involves smooth invertible maps (diffeomorphisms), as presented in this context in [55], [56], [14], [41], [36] and [33].…”
Section: Introductionmentioning
confidence: 99%